Foliar copper on growth and nutrition of coffee seedlings - Lima Dias, kaio Gonçalves; carmo, Davi lopes do; Pozza, Adelia Aziz Alexandre; Pozza, Edson Ampélio; Guimarães, Paulo Tacito Gontijo (Coffee Science - ISSN 1984-3909, 2015)
The objective of this study was to evaluate the effect of different sources and doses of copper (Cu) applied to leaves on growth and nutrition of coffee seedlings. The treatments consisted of combinations of two Cu sources (Cupric Sulfate Ammonium - CSA and Copper Sulfate - CS) and four Cu doses (0, 250, 500 and 1000 g ha-1). The sources of Cu in different doses were dissolved in water, calculated for the application volume of 400 L ha-1. The doses were divided in 3 applications at 20 days. The Cu content and concentration in the leaf, stem, and root in were measured. The dry matter of the leaf, stem, root and total and the utilization, absorption and translocation efficiency, in coffee seedlings were evaluated. In general the Cu content and concentration were obtained for the CS at doses of 250, 500 and 1000 g ha-1 Cu. The maximum increase of total dry matter was 48 and 51 g to CSA and CS, when applied 534 and 668 g ha-1, respectively. The highest utilization and absorption efficiency was found to CSA and CS, respectively. The translocation efficiency was similar for both sources.